DO INVESTORS PAY FOR PURPOSE? A BIBLIOMETRIC ANALYSIS OF SUSTAINABLE BOND PREMIUMS - Fatwasari Soeratno Putri; Doddy Setiawan (Jurnal Bisnis dan Akuntansi, 2025)
This study maps research on sustainable bond pricing, focusing on greenium, socium, and sustainium. Using bibliometric and systematic analyses following PRISMA guidelines, 82 Scopus-indexed articles published between 2019 and 2025 were reviewed. RStudio with Bibliometrix and VOSviewer was used to visualize publication trends and thematic clusters. Results show rapid growth in research since 2019, along with an increase in the ESG market. Most studies identify a small but consistent greenium, while evidence on socium and sustainium remains limited and mixed due to emerging data and market maturity. Environmental factors are the main drivers of bond pricing, while social and governance factors strengthen transparency and investor trust. This study consolidates fragmented literature and outlines ESG-related determinants of sustainable bond premiums. Future research should examine emerging markets and innovative instruments, such as sustainability-linked bonds, to better understand market incentives for sustainable finance.